Chloroplast Translation Initiation Factors Regulate Leaf Variegation and Development. Issue 2 (17th August 2016) - Zheng, Mengdi; Liu, Xiayan; Liang, Shuang; Fu, Shiying; Qi, Yafei; Zhao, Jun; Shao, Jingxia; An, Lijun; Yu, Fei
Abstract : SVR9 and its homolog SVR9L1 encode functionally redundant chloroplast translation initiation factors essential for chloroplast and leaf development in Arabidopsis. Abstract: Chloroplast development requires the coordinated expressions of nuclear and chloroplast genomes, and both anterograde and retrograde signals exist and work together to facilitate this coordination. We have utilized the Arabidopsis yellow variegated ( var2 ) mutant as a tool to dissect the genetic regulatory network of chloroplast development. Here, we report the isolation of a new (to our knowledge) var2 genetic suppressor locus, SUPPRESSOR OF VARIEGATION9 ( SVR9 ). SVR9 encodes a chloroplast-localized prokaryotic type translation initiation factor 3 (IF3). svr9 - 1 mutant can be fully rescued by the Escherichia coli IF3 infC, suggesting that SVR9 functions as a bona fide IF3 in the chloroplast. Genetic and molecular evidence indicate that SVR9 and its close homolog SVR9-LIKE1 (SVR9L1) are functionally interchangeable and their combined activities are essential for chloroplast development and plant survival. Interestingly, we found that SVR9 and SVR9L1 are also involved in normal leaf development. Abnormalities in leaf anatomy, cotyledon venation patterns, and leaf margin development were identified in svr9 - 1 and mutants that are homozygous for svr9 - 1 and heterozygous for svr9l1 - 1 ( svr9 - 1 svr9l1 - 1 /+). Meanwhile, as indicated by the auxin response reporter DR5 : GUS, auxin homeostasis was disturbed in svr9 - 1, svr9 - 1 svr9l1 - 1 /+, and plants treated with inhibitors of chloroplast translation. Genetic analysis established that SVR9 / SVR9L1 -mediated leaf margin development is dependent on CUP - SHAPED COTYLEDON2 activities and is independent of their roles in chloroplast development. Together, our findings provide direct evidence that chloroplast IF3s are essential for chloroplast development and can also regulate leaf development.